Mycorrhizal fungi increase coffee plants competitiveness against Bidens pilosa interference - André Cabral França; Ana Flávia de Freitas; Edson Aparecido dos Santos; Paulo Henrique Grazziotti; Valter Carvalho de Andrade Júnior (Pesquisa Agropecuária Tropical, 2016)
Mycorrhizae provide several benefits to coffee plants. This study evaluated whether these benefits influence the damage caused by the Bidens pilosa competition with coffee seedlings. A randomized blocks design was used, with treatments established in a 2 x 3 factorial scheme (presence and absence of B. pilosa interference in non-inoculated control or plants inoculated with either Claroideoglomus etunicatum or Dentiscutata heterogama). Coffee seedlings were inoculated with fungi spores and developed for 120 days. Then, they were subjected to the interference of B. pilosa for more 120 days, when data were collected for growth traits, mycorrhizal colonization, dry matter and foliar nutrient concentrations in coffee plants. Dry matter and nutrient contents in B. pilosa plants were also evaluated. Inoculation provided better growth and nutrition of coffee plants. The competition with B. pilosa reduced mycorrhizal colonization, height, leaf area, leaf and stem dry mass, root dry weight, number of reproductive branches and levels of P and Fe in the coffee plants. However, the harmful effect of the interference was lower in inoculated coffee plants. The dry mass of B. pilosa decreased under the interference of inoculated coffee plants. The inoculation of C. etunicatum and D. heterogama in Arabica coffee seedlings increases the competitiveness of the crop against B. pilosa interference.